Leaf analysis as a means of assessing the nutrient status of deciduous fruit trees and vines in the Western Cape Province - Beyers, Ewald (Stellenbosch : Stellenbosch University, 2012)
Thesis (DScAgric)--University of Stellenbosch, 1958.